1994
DOI: 10.1242/dev.120.1.83
|View full text |Cite
|
Sign up to set email alerts
|

Primordial germ cell migration in Drosophila melanogaster is controlled by somatic tissue

Abstract: In Drosophila, as in many other organisms, primordial germ cells show invasive and migratory behavior moving from their site of origin to the somatic component of the gonad. At a characteristic time in development, the primordial germ cells pass across the primordium of the gut and migrate on its outer surface toward the mesoderm, where they eventually associate with the somatic tissues of the gonad. Here we demonstrate that the exit and migration are specific behaviors of the primordial germ cells and that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 62 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…and huckebein (hkb) mutants. In these mutants, the PMG epithelium is misdetermined to become hindgut epithelium (Reuter, 1994;Warrior, 1994;Jaglarz and Howard, 1994;Brönner and Jäckle, 1996;. A similar PGC migration phenotype has been shown for mutants of the G-Protein coupled receptor Trapped in endoderm 1 (Tre1) (Kunwar et al, 2003).…”
Section: Pgcs In Embryogenesismentioning
confidence: 58%
See 4 more Smart Citations
“…and huckebein (hkb) mutants. In these mutants, the PMG epithelium is misdetermined to become hindgut epithelium (Reuter, 1994;Warrior, 1994;Jaglarz and Howard, 1994;Brönner and Jäckle, 1996;. A similar PGC migration phenotype has been shown for mutants of the G-Protein coupled receptor Trapped in endoderm 1 (Tre1) (Kunwar et al, 2003).…”
Section: Pgcs In Embryogenesismentioning
confidence: 58%
“…They intercalate the epithelial cells of the PMG pocket and transmigrate the epithelium. Several studies have shown that this process is not exclusively mediated by the PGCs but that it also requires changes in the epithelial cells of the PMG (Jaglarz and Howard 1994;Callaini et al, 1995;Warrior, 1994).…”
Section: Pgcs In Embryogenesismentioning
confidence: 99%
See 3 more Smart Citations